WATERSHED MANAGEMENT- A KEY TO UPLIFT SOCIO- ECONOMIC STATUS IN SHIVALIK FOOTHILL VILLAGES OF INDIA. - Agnihotri, Y.; Samra, J.S. (Journal of Soil and Water Conservation, 2022)
India experiences lot of variation in climatic conditions, soil types, geological fin-mations and, so in the type and standards of scio•cultural living of people. Referring to North western region in particular, the annual rainfall varies between 300 to 2000 mm, land forms on the one extreme are, mountains and highlands while on the other extreme are plains with sand dunes. Shivalik hills, extending over 3 million hectare area in the states of Punjab, Haryana, Himachal Pradesh and Jammu and Kashmir, fall in the northwestern region of the country The annual rainfall received in the region is 1000-1500 mm and the soil temperature regime varies from thermic to hyperthermic. Most of the area is geologically weak and prone to frequent land slides. More than 50 percent of the rainfall ends in runoff and siltation of reservoirs. Paradox of the situtation is that during one part of the year the region has excess water to cause 4 floods, while in an other part of the year the region does not have enough moisture to take winter crops. This is more so because, tubewell and canal irrigation is not possible due to. ground water and topography limitations. Consequently, rainfed agriculture is practices on flat hilly land while degraded forests exist on adjoining hill slopes. Over the years, the area has been marked with low productivity of land as well as animal resources, poverty and environmental degradation. It now appears that such watershed management programmes are the only alternative to give a boost to the economy of the region and uplifiting the social status of the people.